A Single ssRNA Segment Encoding RdRp Is Sufficient for Replication, Infection, and Transmission of Ourmia-Like Virus in Fungi - Wang, Qihua; Mu, Fan; Xie, Jiatao; Cheng, Jiasen; Fu, Yanping; Jiang, Daohong (Frontiers in Microbiology, 2020)
Recently, an increasing number of ourmia-like viruses have been found in fungi; however, the features of these viruses remain unknown. Here, we report a novel ourmia-like virus isolated from Sclerotinia sclerotiorum. This virus, named Sclerotinia sclerotiorum ourmia-like virus 4 (SsOLV4), has a genome 2982 nt in length with a G-pentamer (GGGGG) at the 5'-terminus and a C-pentamer (CCCCC) at the 3'-terminus. The SsOLV4 genome has only one large putative open reading frame (ORF) predicted with both standard codes and mitochondrial codes and encodes an RNA-dependent RNA polymerase (RdRp). SsOLV4 is closely phylogenetically related to Pyricularia oryzae ourmia-like virus 1, with 42% identity between the RdRp amino acid sequences. We constructed full-length cDNA of SsOLV4 and synthesized RNA in-vitro using the T7 RNA polymerase. The synthesized RNA could transfect S. sclerotiorum protoplasts efficiently. We further found that viral RNA could infect mycelia when mixed with PEG buffer. Our study suggests that a novel genus in family Botourmiaviridae should be established for SsOLV4 and other related viruses and demonstrates that one single-stranded RNA segment encoding RdRp is sufficient for ourmia-like viruses in fungi.